Small Signal Stability Analysis of Grid Connected Photovoltaic - Shalom Lim Zhu Aun; Marayati Bte Marsadek; Agileswari K. Ramasamy (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
This paper primarily focuses on the small signal stability analysis of a power system integrated with solar photovoltaics (PV). The test system used in this study is the IEEE 39-bus. The small signal stability of the test system are investigated in terms of eigenvalue analysis, damped frequency, damping ratio and participation factor. In this study, various conditions are analyzed which include the increase in solar PV penetration into the system and load variation. The results obtained indicate that there is no significant impact of solar PV penetration on the small signal stability of large scaled power system.